Visual Field Defect in Pulmonary Tuberculosis Patients with Ethambutol Therapy - Agus Nugroho; Devi Azri Wahyuni (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2016)
Background: Ethambutol (EMB) is important as antimicrobal in the treatment of pulmonary TB which effects ethambutol toxic optic neuropathy (EON). EON can be detected with visual field examination. Research by Vimla Menon stated that toxicity condition of EMB obtained visual field defects by 7.69%. Currently, there is no data on visual field defects in patients with TB treated with (EMB) in Mohammad Hoesin Hospital (RSMH).Methods: This was a cross-sectional observational study with a follow-up studies without controls. The samples of this research was 24 and samples taken consecutive. Visual field examination using the Humphrey Field Analyzer was performed three times: before therapy, 1 month, and 2 months after EMB therapy. Data that can be carried out were analyzed by using SPSS program. Results: Average MD before administration of EMB was -2.36±1.21; average MD after 1 month administration of EMB was -2.35±1.41; and 2 months after was -3.09±1.85. There was a mean change of -0.73±1.43 MD 2 months after EMB administration. Abnormal MD enhancement of 6.52% occured 1 month after EMB administration and 28.26% 2 months after EMB administration. Arcuate visual field defects obtained 9.3% in 2 months after EMB aministration.Conclusion: There was no significant difference in visual field examination on the object before therapy and 1 month after EMB therapy. Examination after obtaining EMB for 2 months, based on the mean deviation of visual field defects, were minimal to moderate; while based on gray scale picture was obtained arcuate visual field defects. Keywords: ethambutol, EON, visual field defect